Design, Synthesis, and Evaluation of Dihydrobenzo[cd]indole-6-sulfonamide as TNF-α Inhibitors - Deng, Xiaobing; Zhang, Xiaoling; Tang, Bo; Liu, Hongbo; Shen, Qi; Liu, Ying; Lai, Luhua (Frontiers in Chemistry, 2018)
Tumor necrosis factor-α (TNF-α) plays a pivotal role in inflammatory response. Dysregulation of TNF can lead to a variety of disastrous pathological effects, including auto-inflammatory diseases. Antibodies that directly targeting TNF-α have been proven effective in suppressing symptoms of these disorders. Compared to protein drugs, small molecule drugs are normally orally available and less expensive. Till now, peptide and small molecule TNF-α inhibitors are still in the early stage of development, and much more efforts should be made. In a previously study, we reported a TNF-α inhibitor, EJMC-1 with modest activity. Here, we optimized this compound by shape screen and rational design. In the first round, we screened commercial compound library for EJMC-1 analogs based on shape similarity. Out of the 68 compounds tested, 20 compounds showed better binding affinity than EJMC-1 in the SPR competitive binding assay. These 20 compounds were tested in cell assay and the most potent compound was 2-oxo-N-phenyl-1,2-dihydrobenzo[cd]indole-6-sulfonamide (S10) with an IC50 of 14 M, which was 2.2-fold stronger than EJMC-1. Based on the docking analysis of S10 and EJMC-1 binding with TNF-α, in the second round, we designed S10 analogues, purchased 7 of them and synthesized 7 new compounds. The best compound, 4e showed an IC50 value of 3 M in cell assay, which was 14-fold stronger than EJMC-1. 4e was among the most potent TNF-α organic compound inhibitors reported so far. Our study demonstrated that 2-oxo-N-phenyl-1,2-dihydrobenzo[cd]indole-6-sulfonamide analogues could be developed as potent TNF-α inhibitors. 4e can be further optimized for its activity and properties. Our study provides insights into designing small molecule inhibitors directly targeting TNF-α and for protein-protein interaction inhibitor design.